Preschool Teachers' Assessment of the Integrative Approach to Environmental Education - Gordana M. Miščević Kadijević; Danimir P. Mandić; Jelena B. Bojanić (University of Belgrade, Teacher Education Faculty, 2019)
An integrated educational activity in preschool context is a system whereby the components from various subject areas operate as a single unit. This paper examines the results of the research on the impact of preschool teachers' professional experience on their assessment of the need for the integration of the Environmental Education content with the contents of other subject areas at preschool level. The sample consisted of 148 respondents: 73 pre-service preschool teachers and 75 in-service preschool teachers. It was found that in-service preschool teachers have a more positive assessment of the need for this integration than pre-service preschool teachers. In addition, there was no correlation between the in-service teachers' duration of service and their assessment of this need. Possible reasons for such findings are given in the paper. Effective integrated activities using the contents of two or more subject areas may be developed through systematic observations of the practical work of in-service preschool teachers and children in their groups. Suggestions for further research are included in the paper as well.